Improvement of electrical properties of ITO thin films by melt-free ultra-short laser crystallization. (18th February 2021) - Farid, N; Sharif, A; Vijayaraghavan, R K; Wang, M; Chan, H; Brunton, A; McNally, P J; Choy, K L; O'Connor, G M
Abstract: We describe a novel solid state crystallisation method for optimising a thin film transparent conductive oxide when deposited on flexible polymer substrates. The method is based on ultra-short non-thermal laser sintering of indium tin oxide (ITO) thin films. In this study, we used commercial ITO thin films deposited on a flexible polyethylene terephthalate substrate with a relatively low melting temperature compared with ITO on glass. We demonstrate the use of laser scanning with high pulse overlapping at fluences seven times less than the threshold required for melting/damage of ITO. The results confirm greater than four times enhancement in the mobility of charge carriers of ITO thin films after laser scanning and sheet resistance can be reduced up to 25%. There is no reduction in optical transparency observed in laser treated samples. Surface morphology and x-ray diffraction analyses confirm the improvement in crystallite sizes by laser sintering, resulting in a greater than 37% increase in grain size due to enhanced crystallization. Comparison of experimental and simulation based on a delayed two temperature model confirms that ITO thin film crystallization occurred at about one-third of the melting temperature of ITO.